2021
DOI: 10.3390/microorganisms9102177
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about Candida auris? State of the Art, Knowledge Gaps, and Future Directions

Abstract: Candida auris has unprecedently emerged as a multidrug resistant fungal pathogen, considered a serious global threat due to its potential to cause nosocomial outbreaks and deep-seated infections with staggering transmissibility and mortality, that has put health authorities and institutions worldwide in check for more than a decade now. Due to its unique features not observed in other yeasts, it has been categorised as an urgent threat by the Centers for Disease Control and Prevention and other international a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 175 publications
(321 reference statements)
0
30
0
10
Order By: Relevance
“…An issue of concern with an anticipated effect on mortality is the emergence and rapid spread of resistant Candida strains, most notably of the Candida auris species, which has preceded the outbreak of SARS-CoV2 but may have been accelerated by the pandemic [ 123 ]. Although the only rarely resistant Candida albicans remains the most commonly isolated Candida species in candidemic non-COVID-19 and COVID-19 patients alike, occasionally, non-susceptible strains of non- albicans Candida species (including Candida glabrata , Candida parapsilosis and Candia kruzei) are increasingly reported and may constitute most bloodstream Candida infections in some instances [ 122 , 124 ]. Candida auris was originally described in 2009 in a Japanese patient with external otitis and has, thenceforth, been isolated in an ever-growing number of countries across the world [ 123 ].…”
Section: Mortality and Fungal Infections In Critically Ill Covid-19 P...mentioning
confidence: 99%
“…An issue of concern with an anticipated effect on mortality is the emergence and rapid spread of resistant Candida strains, most notably of the Candida auris species, which has preceded the outbreak of SARS-CoV2 but may have been accelerated by the pandemic [ 123 ]. Although the only rarely resistant Candida albicans remains the most commonly isolated Candida species in candidemic non-COVID-19 and COVID-19 patients alike, occasionally, non-susceptible strains of non- albicans Candida species (including Candida glabrata , Candida parapsilosis and Candia kruzei) are increasingly reported and may constitute most bloodstream Candida infections in some instances [ 122 , 124 ]. Candida auris was originally described in 2009 in a Japanese patient with external otitis and has, thenceforth, been isolated in an ever-growing number of countries across the world [ 123 ].…”
Section: Mortality and Fungal Infections In Critically Ill Covid-19 P...mentioning
confidence: 99%
“…A new multi-resistant yeast, Candida auris , appeared in 2009 in East Asia and quickly spread around the world, being classified as a serious threat to public health due to infections with high transmissibility and mortality. Recently, epidemiological reports of C. auris outbreaks were released in the context of the COVID-19 pandemic [ 44 ], another very serious public health problem in the world [ 45 ]. In the present study, compound 16 showed antifungal activity against C. auris 01256P CDC, with an MIC of 85.3 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The API ID32C biochemical test system misidentifies C. parapsilosis and other Candida spp., for example, C. sake , which could also result in the failure of treatment, as these two species have different resistance patterns C. sake , contrary to C. parapsilosis , has decreased susceptibility to fluconazole and other triazoles [ 88 ]. Conventional methods often lead to C. famata misidentification [ 87 , 88 ], C. auris is identified with biochemical assays incorrectly in most cases [ 39 , 90 , 91 ].…”
Section: Diagnosis Of Invasive Candidiasismentioning
confidence: 99%
“…The fungus first identified in 2009 in Japan was later found on all continents except Antarctica [ 36 , 37 , 38 ]. This species is closely related to the C. haemulonii complex and has five geographically and genetically distant clades [ 39 , 40 ]. The rise in cases occurred simultaneously in different regions [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%